Marketing Mix Analysis of Banana Chips in the Barokah Banana Chips Household Industry, Unaaha District, Konawe Regency - Saiful Jihad; Surni; Abdi (International journal of technology and education research, 2025)
This study aims to examine the marketing mix implemented by the banana chips business